Thin-film a-Si:H solar cells processed on aluminuminduced texture (AIT) glass superstrates: Prediction of light absorption enhancement - Sahraei, Nasim; Peters, Marius; Venkataraj, Selvaraj; Aberle, Armin G.; Calnan, Sonya; Ring, Sven; Stannowski, Bernd; Schlatmann, Rutger; Stangl, Rolf (Applied Optics, 2015)
Light scattering superstrates are important for thin-film a-Si:H solar cells. In this work, aluminum-induced texture (AIT) glass, covered with nonetched Al-doped ZnO (AZO), is investigated as an alternative to the commonly used planar glass with texture-etched AZO superstrate. Four different AIT glasses with different surface roughnesses and different lateral feature sizes are investigated for their effects on light trapping in a-Si:H solar cells. For comparison, two reference superstrates are investigated as well: planar glass covered with nonetched AZO and planar glass covered with texture-etched AZO. Single-junction a-Si:H solar cells are deposited onto each superstrate, and the scattering properties (haze and angular resolved scattering) as well as the solar cell characteristics (current-voltage and external quantum efficiency) are measured and compared. The results indicate that AIT glass superstrates with nonetched AZO provide similar, or even superior, light trapping than the standard reference superstrate, which is demonstrated by a higher short-circuit current Jsc and a higher external quantum efficiency. Using the trapped light fraction δ, a quantity based on the integrated light scattering at the AZO/a-Si:H interface, we show that Jsc linearly increases with δ in the scattering regime of the samples, regardless of the type of superstrate used.
CRIS-Team Scopus Importer:2023-03-07